Evaluation of Analgesia, Tolerance, and the Mechanism of Action of Morphine-6-O-Sulfate Across Multiple Pain Modalities in Sprague-Dawley Rats. (September 2017) - Yadlapalli, Jai Shankar K.; Dogra, Navdeep; Walbaum, Anqi W.; Wessinger, William D.; Prather, Paul L.; Crooks, Peter A.; Dobretsov, Maxim
Abstract : BACKGROUND: Morphine-6- O -sulfate (M6S) is a mixed μ/δ-opioid receptor (OR) agonist and potential alternative to morphine for treatment of chronic multimodal pain. METHODS: To provide more support for this hypothesis, the antinociceptive effects of M6S and morphine were compared in tests that access a range of pain modalities, including hot plate threshold (HPT), pinprick sensitivity threshold (PST) and paw pressure threshold tests. RESULTS: Acutely, M6S was 2- to 3-fold more potent than morphine in HPT and PST tests, specifically, derived from best-fit analysis of dose–response relationships of morphine/M6S half-effective dose (ED50 ) ratios (lower, upper 95% confidence interval [CI]) were 2.8 (2.0–5.8) in HPT and 2.2 (2.1, 2.4) in PST tests. No differences in analgesic drug potencies were detected in the PPT test (morphine/M6S ED50 ratio 1.2 (95% CI, 0.8–1.4). After 7 to 9 days of chronic treatment, tolerance developed to the antinociceptive effects of morphine, but not to M6S, in all 3 pain tests. Morphine-tolerant rats were not crosstolerant to M6S. The antinociceptive effects of M6S were not sensitive to κ-OR antagonists. However, the δ-OR antagonist, naltrindole, blocked M6S-induced antinociception by 55% ± 4% (95% CI, 39–75) in the HPT test, 94% ± 4% (95% CI, 84–105) in the PST test, and 5% ± 17% (95% CI, −47 to 59) or 51% ± 14% (95% CI, 14–84; 6 rats per each group) in the paw pressure threshold test when examined acutely or after 7 days of chronic treatment, respectively. CONCLUSIONS: Activity via δ-ORs thus appears to be an important determinant of M6S action. M6S also exhibited favorable antinociceptive and tolerance profiles compared with morphine in 3 different antinociceptive assays, indicating that M6S may serve as a useful alternative for rotation in morphine-tolerant subjects. Abstract : Published ahead of print May 4, 2017.